Al-A’immah Min Quraisy Antara Doktrin dan Kebutuhan Sosial - Ahwan Mukarrom (Ulumuna, 2008)
This article elaborates the conflict among the three fractions began from big dispute between Anshar and Abu Bakar and his associates (after Rasulullah’s death on 8 June 632). Abu Bakar solved the dispute through diplomacy and the jargon saying that al-a’immah min quraisy. However, the inter conflict in Muhajirin group, between Abu Bakar and Ali who had the same Quraisy root, was difficult to solve. The dispute between the two powers affected Muslim ummah seriously and greatly. Later on, each of them had faithful followers with their contradictory political thoughts based on naqly and aqly knowledge. In fact, their controversial political thoughts have rooted strongly and spread over the world. Therefore, it is relevant to reflect Rasulullah’s saying, related by Muslim, in Ijabah Mosque in Medina. In that hadist it is said that only two of three Rasulullah’s appeals for his ummah are accepted, the rest is rejected.